Pathways to culturally sensitive tourism policies and practices - Lüthje, Monika; Höckert, Emily; Kugapi, Outi (2023)
Market-driven development, outsider operators with little knowledge of Indigenous or other local cultures, stereotypical representations and cultural appropriation are common interrelated problems in Arctic tourism. This paper brings together discussions of social practices and cultural sensitivity in order to gain a better understanding of how more inclusive, legitimate and effective sustainable tourism policies can be formulated. Our research draws on a wide range of stakeholder interviews and benchmarking in Arctic Finland, Sweden, Norway, Greenland and Canada. It focuses on two bundles of culturally sensitive practices that tourism companies utilise, according to our empirical material: reciprocal practices enhancing collaboration and respectful practices related to authenticity. Moreover, we identify local knowledge as the connecting element between these two bundles. The paper suggests cultural sensitivity as a novel framework for tourism policymaking and sustainable tourism practices. Our research was supported by the Northern Periphery and Arctic Programme 2014–2020, under Project No. 274 – Culturally Sensitive Tourism in the Arctic (ARCTISEN). We would like to acknowledge ARCTISEN project partners for their support and commitment to developing culturally sensitive tourism in the Arctic.